Voltage stability control of wind farm using PMSG based variable speed wind turbine - Rosyadi, M.; Muyeen, S.M.; Takahashi, R.; Tamura, J. (2012)
In this paper, combination system of squirrel cage induction generator based fixed speed wind turbine and permanent magnet synchronous generator based variable speed wind turbine is considered to improve voltage stability of a wind farm. A suitable control scheme for back-to-back converter of variable speed permanent magnet synchronous generator is developed to improve the voltage stability as well as reactive power compensation of the fixed speed induction wind generator in cases of disturbed and normal conditions. The transient and steady state conditions are analyzed using PSCAD/ EMTDC, and it is concluded that the proposed topology is effective to enhance the voltage stability of wind farm for network fault disturbance and fluctuating wind speed.